1997
DOI: 10.1111/j.1469-8749.1997.tb07480.x
|View full text |Cite
|
Sign up to set email alerts
|

Disability due to restrictions in childhood epilepsy

Abstract: Parents and doctors impose restrictions on children with epilepsy to avoid seizure‐related injuries. We intended to quantify disability due to such restrictions by using a newly developed parent‐completed 10‐item scale (The Hague Restrictions in Childhood Epilepsy Scale, HARCES). Parents reported disability on at least one item of the HARCES in 83% of 122 children with epilepsy and a remission from seizures for less than 1 year. Psychometric analysis of the scale's reliability demonstrated good internal consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 12 publications
0
33
0
3
Order By: Relevance
“…Interestingly, Norrby et al (24) found that children with controlled epilepsy and no obvious neurodeficits did not differ from aged-matched controls when describing themselves using 39 bipolar adjectives and a VAS of well-being. Austin et al (25), Hoare and Kerley (26), and Carpay et al (27) addressed selected concerns of children with epilepsy, such as relationships with siblings, stigma, self-esteem, and restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Norrby et al (24) found that children with controlled epilepsy and no obvious neurodeficits did not differ from aged-matched controls when describing themselves using 39 bipolar adjectives and a VAS of well-being. Austin et al (25), Hoare and Kerley (26), and Carpay et al (27) addressed selected concerns of children with epilepsy, such as relationships with siblings, stigma, self-esteem, and restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, Herranz and Casas [18] (see also Casas-Fernàndez [19]) constructed an 8-item scale asking the parents to evaluate their child with epilepsy. Carpay et al [20,21] proposed scales to be completed by parents of CWE measuring seizures' severity and side effects of anti-epileptic drugs [20] and a 10-item scale evaluating epilepsy-related restrictions in a child's daily activities (for an application of the restrictions scale, see Van Empelen et al [22]). Sabaz et al [23,24] proposed a 91-item measure of QoL for CWE.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several scales have been developed to investigate quality of life (QOL) in children and adolescents with this condition (Breau, Camfield, Camfield, & Breau, 2008;Camfield, Breau, & Camfield, 2001Carpay et al, 1997;Cramer et al, 1999;De Souza, Da Mota Gomes, & Da Costa Fontelelle, 2005;Herranz & Casas, 1996;Hoare & Russell, 1995;McEwan, Espie, & Metcalfe, 2004;Montanaro, Battistella, Boniver, & Galeone, 2004;Ronen, Streiner, Rosenbaum, & Canadian Pediatric Epilepsy Network, 2003;Townshend et al, 2008). QOL was defined by the World Health Organization (WHO) in 1993 as "an individual's perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns" (p. 153).…”
mentioning
confidence: 99%